High strain and long duration cycling behavior of laser welded NiTi sheets. (February 2016) - Oliveira, J.P.; Miranda, R.M.; Schell, N.; Braz Fernandes, F.M.
Graphical abstract: Highlights: Cycling at high strains and for a high number of cycles in laser welded NiTi sheets. Lower heat input implied higher superelastic recovery. Welds were successfully cycled 600 times, 110–130 MPa below their tensile strength. Martensite in the thermal affected regions lowers the superelastic plateau. Abstract: The use of NiTi in complex shaped components for structural applications is limited by the material cost and machinability and adequate joining techniques have been investigated to minimize the thermal cycle effect on the superelastic and shape memory effects exhibited by NiTi. Laser welding is the most used joining process for this material. However, existing studies mainly address the functional properties of laser welded NiTi wires, and the superelastic cycling tests are limited to either a low number of cycles (maximum 100) or to low strains (below 6%). This paper discusses the results of the cycling behavior exhibited by laser butt welded 1 mm thick NiTi plates, when tested to high strains (up to 10%) and for a large number of cycles (600). The superelastic effect was observed and the microstructural changes induced by the laser welding procedure, namely the extension of the thermal affected regions, were seen to influence the evolution of the accumulated irrecoverable strain. Thus, it is possible, by controlling the heat input introduced during welding, to tune the maximum superelastic recovery presented by NiTi laser welds.